Evaluation of an automotive wiper noise & vibration characteristics using numerical approach - Abu Bakar, Abd. Rahim (Faculty of Mechanical Engineering, 2009)
As modern passenger cars become increasingly quieter and comfort, automotive windscreen wiper noise and vibration become more noticeable. As a result of the market information survey, most complaints about the wiper concern operation noise. Wiper vibration and noise is classified into three main categories namely, squeal noise, chattering, and reversal noise. Squeal noise is a high-frequency vibration of about 1000 Hz. Chattering noise is a lowfrequency vibration of 100Hz or less and reversal noise is an impact sound with a frequency of 500 Hz or less produced when the wiper reverses. Typically, noise and vibration study of the automotive windscreen wiper has been carried out by experimental, analytical and numerical approaches. This report describes evaluation of noise and vibration that generated by an automotive windscreen wiper using numerical approach via finite element method. In doing so, two types of test are conducted i.e. modal testing for individual wiper components and noise and vibration test to identify noise category for a selected passenger car windscreen wiper. Later, a 3-dimensional (3D) finite element (FE) model of the windscreen wiper assembly is developed. This FE model is then validated at the component level using modal analysis in order to ensure that dynamic characteristics of the FE model close to a real windscreen wiper. In order to evaluate characteristics of noise and vibration of the windscreen wiper, complex eigenvalue analysis that made available in ABAQUS is employed. It is found that the windscreen wiper generates noise at frequency around 11 Hz which is identified as chatter and the predicted frequency is fairly close with measured frequency obtained in the experiment. This chatter noise is dominated by bending mode of the wiper blade. Having found the characteristics of the windscreen wiper noise, several structural modifications are proposed to the rubber blade and simulated once again. There are three modifications that capable of preventing noise and vibration in the windscreen wiper. This finding could help car makers to design quiet and effective windscreen wiper and in turn to produce quieter and comfort passenger cars.